Validating and expanding the Baveno VI criteria for esophageal varices in patients with advanced liver disease: a multicenter study - Protopapas, Adonis A. (Ann Gastroenterol, 2020)
INTRODUCTION: According to the Baveno VI workshop, patients with compensated advanced liver disease, platelet count (PLT) >150,000/μL and liver stiffness measurement (LSM) <20 kPa can avoid screening endoscopy for high-risk varices (HRVs). The purpose of this study was to validate these criteria in a multicenter Greek cohort and consider other approaches that may further decrease the number of endoscopies. METHODS: We prospectively enrolled patients with advanced liver disease (defined as LSM >12 kPa) and evaluated them according to the Baveno VI criteria. Exclusion criteria were splanchnic vein thrombosis, use of β-blockers, and esophageal varices. Screening endoscopy was conducted within 6 months of liver stiffness and laboratory measurements. RESULTS: One-hundred seven consecutive patients were enrolled in the study to undergo LSM and screening endoscopy. Of these, 13 met the Baveno VI criteria (12.1%); none of the latter had HRVs. Additional parameters were examined, among which the quotient PLT/log(10)LSM exhibited the largest area under the curve; concerning the latter, values ≤122,000 μL(-1) x kPa(-1) predicted high-risk varices with 100% sensitivity and negative predictive value (NPV), preventing 20.6% of patients from unneeded screening endoscopy (P=0.003). Moreover, values ≤92,000 μL(-1) x kPa(-1) exhibited 86% sensitivity and 94% NPV, preventing 44.9% of patients from unneeded screening endoscopy (P=0.001), while maintaining a tolerable percentage of overlooked patients with HRVs (6.3%). CONCLUSIONS: The Baveno VI criteria were successfully validated in our study. The quotient PLT/log(10)LSM can be used to further decrease the number of screening endoscopies in patients with advanced liver disease.